1974
DOI: 10.1128/aac.6.6.691
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetics of Metronidazole as Determined by Bioassay

Abstract: The pharmacokinetics of metronidazole, a drug effective in vitro against most anaerobic bacteria and promising in treating anaerobic infections, are described. Serum and urine levels after single and multiple doses in 10 adult male volunteers were measured by an agar well diffusion bioassay using clostridial species as the test organisms under anaerobic conditions. Peak serum levels averaged 11.5 ,ug/ml and 6.2 ug/ml after single 500-mg and 250-mg doses, respectively. Renal clearance was only 10.2 ml/min per 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
37
0
1

Year Published

1976
1976
2012
2012

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 94 publications
(41 citation statements)
references
References 8 publications
3
37
0
1
Order By: Relevance
“…The half-lives determined with bioassays (10,14,17) were higher, presumably due to the biological activity of the hydroxy metabolite (18). The serum levels of this metabolite described above agree well with earlier observations (7,8).…”
Section: Resultssupporting
confidence: 80%
“…The half-lives determined with bioassays (10,14,17) were higher, presumably due to the biological activity of the hydroxy metabolite (18). The serum levels of this metabolite described above agree well with earlier observations (7,8).…”
Section: Resultssupporting
confidence: 80%
“…These results are in good agreement with the studies of Taylor et al [33], who used a centrifuge-type ultrafiltra tion method. Other investigators found a lower protein binding [22,24], It is unlikely that at therapeutic concentrations the bind ing of metronidazole to plasma albumin ex erts an appreciable influence on pharma cokinetics and thus pharmacodynamics, since the association constant is less than 104M-1. This property and the small size of the metronidazole molecule favors a rap id diffusion to all tissues and fluid compart ments [3.…”
Section: Discussionmentioning
confidence: 99%
“…This is in ac cordance with results of other authors [14,31], who estimated metronidazole with chemical methods in the urine of nonpreg nant women. Using the bioassay, the ob served urine concentrations and recovery were lower [22]. Chemical methods deter mined the unchanged drug in urine as well as a significant quantity of biologically inac tive metabolites [22,31,33], In all our cases the urinary concentrations were chemotherapeutically effective.…”
Section: Discussionmentioning
confidence: 99%
“…The metabolism of metronidazole and the basis of its activity are still poorly understood. Recently a bioassay utilizing Clostridium was described as being useful for determining the concentration of metronidazole in body fluids (7). The purpose of this report is to present findings which suggest that this bioassay may be restricted in its usefulness.…”
mentioning
confidence: 83%